Breast Cancer Patients' Experience and Wishes Regarding Communication on Sexual Health: The BEROSE Study. (3rd July 2022) - Aupomerol, M.; Chaltiel, D.; Pautier, P.; Wehrer, D.; Véron, L.; Degousée, L.; Fasse, L.; Guéroult-Accolas, L.; Di Meglio, A.; Scotté, F.; De-Jesus, A.; Vaz-Luis, I.; et al.
Abstract: BEROSE is a single-center observational study, which aimed to determine the proportion of women with breast cancer who received information on sexual health from health professionals throughout their whole care pathway. A total of 318 women with all stages of breast cancer (30% metastatic) and at different time interval from diagnosis (up to 7 years) participated to the survey. Sixty-five percent of women reported that they had not received any information about sexual health over the whole care. Increased awareness among the healthcare professionals and particularly the oncology community is needed to discuss sexual health in women with breast cancer.